Penerapan Media Podcast Dalam Pembelajaran Menulis Teks Cerpen Pada Siswa Kelas XI SMA Negeri 1 Grobogan Tahun Pelajaran 2022/2023 - Lilik Andriyan; Siti Ulfiyani; Zainal Arifin (Simpati, 2024)
This research aims to describe the application of podcast media in learning to write short story texts in class XI of SMA Negeri 1 Grobogan for the 2022/2023 academic year. This type of research is descriptive qualitative. The data collection techniques used are observation techniques, interview techniques, and also documentation techniques. Meanwhile, the background to this research is class XI students at SMA Negeri 1 Grobogan who are considered very active and thirsty for technology-based media. The research carried out obtained valid data and as expected, that the lesson went well. Apart from going well based on the data that has been collected, the activities carried out for 2X45 minutes are in line with the principles of good learning, therefore this research on the application of Podcast media in learning to write short story texts for class XI students at SMA Negeri 1 Grobogan can be said to be implemented well.